Occupational exposure to Aspergillus section Fumigati: tackling the knowledge gap in Portugal - Viegas, Carla (2021)
Project “Occupational exposure of ambulance drivers to bioburden” (IPL/2020/BIO-AmbuDrivers_ESTeSL).